2000
DOI: 10.1034/j.1600-079x.2001.280201.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of melatonin on free radical‐induced changes in rat pancreatic beta‐cells in vitro

Abstract: Free radicals may produce cytotoxicity to pancreatic islets under pathophysiological conditions. The aim of our in vitro investigations was to compare functional and morphological changes in pancreatic beta-cells induced by reactive oxygen species (ROS) generated by alloxan or xanthine oxidase/hypoxanthine (XO/HX), respectively. We demonstrate that short-term exposure to alloxan or to XO/HX leads to a temporarily elevated insulin release from isolated pancreatic islets. On application of alloxan, this effect i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0
4

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 32 publications
1
38
0
4
Order By: Relevance
“…Wollheim's group found in rat islets that H 2 O 2 and alloxan, another agent like DEM that can increase intracellular H 2 O 2 , caused a rapid and transient elevation of intracellular Ca 2ϩ accompanied by insulin release at basal nonstimulatory glucose concentrations (39,40). Similarly, Ebelt et al (41) reported that short-term exposure of isolated rat islets to alloxan and xanthine oxidase/hypoxanthine, a well-known ⅐O 2 Ϫ generating system, evoked an acute elevation in insulin release. Additional indirect support for the notion that ROS in ␤-cells might contribute to GSIS also comes from Leloup et al (42), who recently reported that mitochondrial ROS are required for hypothalamic glucose sensing.…”
Section: Discussionmentioning
confidence: 98%
“…Wollheim's group found in rat islets that H 2 O 2 and alloxan, another agent like DEM that can increase intracellular H 2 O 2 , caused a rapid and transient elevation of intracellular Ca 2ϩ accompanied by insulin release at basal nonstimulatory glucose concentrations (39,40). Similarly, Ebelt et al (41) reported that short-term exposure of isolated rat islets to alloxan and xanthine oxidase/hypoxanthine, a well-known ⅐O 2 Ϫ generating system, evoked an acute elevation in insulin release. Additional indirect support for the notion that ROS in ␤-cells might contribute to GSIS also comes from Leloup et al (42), who recently reported that mitochondrial ROS are required for hypothalamic glucose sensing.…”
Section: Discussionmentioning
confidence: 98%
“…Pankreas üzerinde yapılmış çalışmalarda da, melatoninin pankreasta koruyucu etkisi olduğu göste-rilmiştir [21]. Pankreasta oksidatif stresi artırmaya yönelik diğer deneysel modellemelerde de antioksidanların koruyucu etkileri araştırılmıştır.…”
Section: Discussionunclassified
“…Furthermore, the cytotoxic action of alloxan is mediated mainly by the generation of reactive oxygen species (ROS) (Dahech, Belghith et al 2011). ROS produce fragmentation and damage of DNA of β -cells exposed to alloxan (Ebelt, Peschke et al 2000).…”
Section: Discussion:-mentioning
confidence: 99%